The Impact of Supporting Parents of Children with Disabilities in the UAE - Thabet, Rawy A. (2020)
This paper intends to measure the impact of a training programme on parents/caregivers of children with disabilities. This training programme was designed by academics at the British University in Dubai with support from the Al Jalila Foundation (AJF), a charitable organization located in Dubai, the United Arab Emirates (UAE). This research measures how this programme helps those parents and caregivers to cope with the challenging behaviours of their children with different types of disabilities, with a particular focus on people from Ras Al-Khaimah, an emirate of the seven emirates that form the UAE. Mixed methods were used to measure such impact. To this end, 31 parents/caregivers were interviewed and completed pre and post questionnaires. The results suggest that this programme had a positive impact on the quality of life of the participants. The findings also show that there is a pressing need and increasing demand for more training programmes to support parents/caregivers of children with disabilities to better cope with the challenging behaviours. A set of recommendations for further practice is offered to support decision makers in the area of empowerment of people with disabilities and their families/caregivers in the region.